Tourism awareness of merchant souvenirs in Bukittinggi City - Wirdatul 'Aini; Ismaniar Ismaniar; Hayatunnufus Hayatunnufus (International Conferences on Educational, Social Sciences and Technology)
The purpose of the study is described about tourism awareness and learning of souvenir merchants. The research approach used is qualitative. The subject is souvenir merchant which determined by the government. Data collection techniques used were observations and conducted interviews with merchants souvenir. Interviews were conducted by the people who were around them. Especially, who knew their participation for advancing the tourism area. The research findings are: (1) the description about tourism awareness of souvenir merchant, a part of them were giving the suggestion to increase the security in tourist area, (2) a small number of them was participated in maintaining the cleanliness facilities, maintaining the orderliness, cleanliness of the tourist area as a market, (3) a small number of them, less on serving the customers well, and less pacakaged product, (4) Just a little program available to learn the tourism awareness of them conducted by the government.